Diagnostic accuracy of sequential co-registered PET + MR in comparison to PET/CT in local thoracic staging of malignant pleural mesothelioma. (April 2016) - Martini, Katharina; Meier, Andreas; Opitz, Isabelle; Weder, Walter; Veit-Haibach, Patrick; Stahel, Rolf A.; Frauenfelder, Thomas
Highlights: PET + MR is comparable to PET/CT in TN-staging of Malignant Pleural Mesothelioma. PET + MR has significantly higher diagnostic confidence compared to PET/CT (p = 0003). MR allows for a better morphologic characterization compared to CT. Abstract: Purpose: To investigate the diagnostic accuracy of sequential co-registered PET + MR (PET + MR) for local staging of malignant pleural mesothelioma (MPM) compared to PET/CT. Material and methods: In a prospective clinical trial 34 consecutive patients (median age 66 years; range 40–79 years; 1 female, 33 male) with known MPM, who underwent PET/CT and PET + MR exams for either staging or re-staging/follow-up were evaluated. Imaging was conducted using a tri-modality PET/CT-MR set-up (Discovery PET/CT 690, 3T Discovery MR 750w, both GE Healthcare, Waukesha, WI, USA). In 26 cases histopathology served as standard of reference. Two independent readers evaluated images for T and N stage, confidence level (sure to unsure; 1–3) and subjective overall image quality (very good to non-diagnostic; 1–4). Inter-observer agreement of T and N stages (Cohen's kappa) and interclass correlation coefficient (ICC) between PET/CT vs. PET + MR was calculated. Results: Inter observer agreement for evaluation of T and N Stage in PET/CT images was excellent (k = 0.844 and k = 0.824, respectively), whereas PET + MR imaging showed substantial agreement in T and N stage (k = 0.729 and k = 0.691, respectively). The ICC of PET/CT vs. PET + MR for evaluation of both, T and N Stage, was excellent (ICC = 0.951 and ICC = 0.93, respectively). Diagnostic confidence was scored significantly higher in PET + MR compared to PET/CT (mean score = 1.66 and 1.93, respectively; p = 0.004). Image quality was diagnostic for all image series. Comparing pT and pN stage vs cT and cN stage (n = 26 cases), both imaging modalities showed excellent agreement for T stage (ICCPET + MR = 0.888 vs. ICCPET/CT = 0.853, respectively) and substantial to moderate agreement for N stage (ICCPET + MR = 0.683 vs. ICC = 0.595PET/CT, respectively). Conclusion: Our findings suggest that diagnostic accuracy of PET + MR is comparable to PET/CT for local staging of MPM, whereas radiologists felt significantly more confident staging PET + MR compared to PET/CT images (p = 0003), using dedicated sequences.